A Nature-Inspired Nrf2 Activator Protects Retinal Explants from Oxidative Stress and Neurodegeneration - Maria Grazia Rossino; Rosario Amato; Marialaura Amadio; Michela Rosini; Filippo Basagni; Maurizio Cammalleri; Massimo Dal Monte; Giovanni Casini (MDPI AG, 2021)
Oxidative stress (OS) plays a key role in retinal dysfunctions and acts as a major trigger of inflammatory and neurodegenerative processes in several retinal diseases. To prevent OS-induced retinal damage, approaches based on the use of natural compounds are actively investigated. Recently, structural features from curcumin and diallyl sulfide have been combined in a nature-inspired hybrid (NIH1), which has been described to activate transcription nuclear factor erythroid-2-related factor-2 (Nrf2), the master regulator of the antioxidant response, in different cell lines. We tested the antioxidant properties of NIH1 in mouse retinal explants. NIH1 increased Nrf2 nuclear translocation, Nrf2 expression, and both antioxidant enzyme expression and protein levels after 24 h or six days of incubation. Possible toxic effects of NIH1 were excluded since it did not alter the expression of apoptotic or gliotic markers. In OS-treated retinal explants, NIH1 strengthened the antioxidant response inducing a massive and persistent expression of antioxidant enzymes up to six days of incubation. These effects resulted in prevention of the accumulation of reactive oxygen species, of apoptotic cell death, and of gliotic reactivity. Together, these data indicate that a strategy based on NIH1 to counteract OS could be effective for the treatment of retinal diseases.